Benchmarking the Activity, Stability, and Inherent Electrochemistry of Amorphous Molybdenum Sulfide for Hydrogen Production. Issue 8 (4th January 2019) - Escalera‐López, Daniel; Lou, Zhiheng; Rees, Neil V.
Abstract: Anodically electrodeposited amorphous molybdenum sulfide (AE‐MoS x ) has attracted significant attention as a non‐noble metal electrocatalyst for its high activity toward the hydrogen evolution reaction (HER). The [Mo3 S13 ] 2− polymer‐based structure confers a high density of exposed sulfur moieties, widely regarded as the HER active sites. However, their intrinsic complexity conceals full understanding of their exact role in HER catalysis, hampering their full potential for water splitting applications. In this report, a unifying approach is adopted accounting for modifications in the inherent electrochemistry (EC), HER mechanism, and surface species to maximize the AE‐MoS x electroactivity over a broad pH region (0–10). Dramatic enhancements in HER performance by selective electrochemical cycling within reductive (overpotential shift, ηHER  ≈ −350 mV) and electro‐oxidative windows (ηHER  ≈ −290 mV) are accompanied by highly stable performance in mildly acidic electrolytes. Joint analysis of X‐ray photoelectron spectroscopy, Raman, and EC experiments corroborate the key role of bridging and terminal S ligands as active site generators at low pH, and reveal molybdenum oxysulfides (Mo 5+ O x S y ) to be the most active HER moiety in AE‐MoS x in mildly acidic‐to‐neutral environments. These findings will be extremely beneficial for future tailoring of MoS x materials and their implementation in commercial electrolyzer technologies. Abstract : The interplay of inherent electrochemistry and surface species is investigated to maximize hydrogen production on amorphous MoS x across the pH spectrum . The most active HER species are found to be the S‐depleted molybdenum oxysulfide moieties, only stable in mildly acidic to neutral pHs (4 ≤ pH < 7). The simultaneous cleaving and dissolution of bridging and terminal S ligands is electrochemically proved.